An International Comparison of Consumption Functions - Yang, Charles Yneu (The Review of Economics and Statistics, 1964)
Introduction JN spite of the voluminous studies that have been made on the theory of the consumption function, one important question remains unanswered. Does the Keynesian theorem of consumer behavior operate in any modern community as Keynes claimed it would? ' The first section of this paper will be devoted to testing the Keynesian hypotheses: (1) the level of current income is the main determinant of the level of current consumption in the short run, and (2) the marginal propensity to consume is less than unity. In the second section, we shall examine factors affecting the differences in aggregate consumption ratios of various nations. While much effort has been spent on study of the aggregate consumption function of the United States, our knowledge of the consumption patterns of countries in the rest of the free world, particularly of less advanced countries, continues to lag.2 The relative scarcity of research in this area has been due primarily to the absence of reliable data. Until the introduction of a uniform national account system by the United Nations in 1947, national income data were virtually non-existent except for the highly developed countries.3 As reports of the member nations have been published for a number of years, sufficient data are now available to calculate and compare the aggregate consumption functions of various nations. The following criteria were used in selecting countries for this study: